Engineering Design Process of Arduino Uno-based Smart Classroom Technology - Deny Nusyirwan; Eko Prayetno; Sumantri; Prasetya Perwira Putra Perdana (Jurnal Inovasi Teknologi, 2020)
The important role of higher education in the 21 st century is to participate in educating the public through the development of research results, therefore the Department of Electrical Engineering at the Raja Ali Haji Maritime University emphasizes the importance of implementing an engineering design process to be able to produce technology-based innovations needed by society. This research is a form of higher education contribution in improving student learning outcomes in elementary schools, through the provision of facilities in classrooms. Technology in schools is one of the driving forces for advancing education in schools and is expected to be able to change the mindset of students at Government Primary School (SD Negeri) 011 Tanjungpinang Timur to get to know technology more. It can be said that to realize the perfection of students, in addition to learning activities, supporting facilities are also needed at school according to technological developments. It is hoped that the facilities in technology-based schools will be able to encourage students to be more enthusiastic about learning, have a desire to know developments in the world of technology and change their mindset towards the use of technology in everyday life. From the observations, it was found that the main problem was the minimal use of technology in schools. With these technological problems, this study will design technology-based prototypes, namely smart classrooms based on Arduino Uno, with the aim of making it easier for teachers to turn on electrical equipment in class without direct contact with switches. The intelligent classroom system design uses the Arduino uno as a controller, the HC-06 bluetooth module as a liaison for the user's android with the Arduino Uno, and the boarduino application as a command from the android via bluetooth transmission media